Effects of FGF21 overexpression in osteoporosis and bone mineral density: a two-sample, mediating Mendelian analysis - Liu, Jingjing; Jiang, Jun; Li, Yunjia; Chen, Qiaojun; Yang, Ting; Lei, Yanfa; He, Zewei; Wang, Xiaowei; Na, Qiang; Lao, Changtao; Luo, Xinlei; Yang, Lirong; et al. (Frontiers in Endocrinology, 2024)
Abstract： Objective Fibroblast growth factor 21 (FGF21) is a secreted protein that regulates body metabolism. In recent years, many observational studies have found that FGF21 is closely related to bone mineral density and osteoporosis, but the causal relationship between them is still unclear. Therefore, this study used two-sample, mediated Mendelian randomization (MR) analysis to explore the causal relationship between FGF21 and osteoporosis and bone mineral density. Methods We conducted a two-sample, mediator MR Analysis using genetic data from publicly available genome-wide association studies (GWAS) that included genetic variants in the inflammatory cytokine FGF21, and Total body bone mineral density, Heel bone mineral density, Forearm bone mineral density, Femoral neck bone mineral density, osteoporosis. The main analysis method used was inverse variance weighting (IVW) to investigate the causal relationship between exposure and outcome. In addition, weighted median, simple median method, weighted median method and MR-Egger regression were used to supplement the explanation, and sensitivity analysis was performed to evaluate the reliability of the results. Results MR Results showed that FGF21 overexpression reduced bone mineral density: Total body bone mineral density (OR=0.920, 95%CI: 0.876-0.966), P=0.001), Heel bone mineral density (OR=0.971, 95%CI (0.949-0.993); P=0.01), Forearm bone mineral density (OR=0.882, 95%CI(0.799-0.973); P=0.012), Femoral neck bone mineral density (OR=0.952, 95%CI(0.908-0.998), P=0.039); In addition, it also increased the risk of osteoporosis (OR=1.003, 95%CI (1.001-1.005), P=0.004). Sensitivity analysis supported the reliability of these results. The effect of FGF21 overexpression on osteoporosis may be mediated by type 2 diabetes mellitus and basal metabolic rate, with mediating effects of 14.96% and 12.21%, respectively. Conclusions Our study suggests that the overexpression of FGF21 may lead to a decrease in bone mineral density and increase the risk of osteoporosis, and the effect of FGF21 on osteoporosis may be mediated through type 2 diabetes and basal metabolic rate. This study can provide a reference for analyzing the potential mechanism of osteoporosis and is of great significance for the prevention and treatment of osteoporosis. Key words：Fibroblast growth factor 21; osteoporosis; GWAS; Mendelian randomization.